Mycobacterial spindle cell pseudotumor in a woman with HIV - Krause, John R. (Proc (Bayl Univ Med Cent), 2020)
Mycobacterial spindle cell pseudotumor (MSP) is a rare benign entity characterized by tumor-like proliferations of spindle-shaped histiocytes containing acid-fast positive mycobacteria. MSPs tend to occur predominantly in immunocompromised individuals and are concerning for a malignant neoplasm. We report a case of MSP occurring in a woman with human immunodeficiency virus and a tumor-like mass in the abdomen. A subsequent biopsy revealed MSP, which was successfully treated with antimycobacterial therapy.